Optimization of Technical Calculation of Precast Wall Application for Kawo Secondary Canal Improvement in Sempor Irrigation Area, Kebumen, Central Java - Septiani, S; Nanda, Mahdika Putra; Piera, Nuno (Universitas Islam Sultan Agung, 2024)
This study aims to perform technical calculations using precast lining in the repair of secondary channels. The planning data used included a concrete grade of fc 18.68 MPa and a reinforcement grade of fy 500 MPa. The service condition analysis was carried out by taking into account the loading during the most critical condition, where the channel is empty and active soil pressure and external water pressure are the main loads. The fixed load calculation was the main focus, where the active earth pressure (PD) was calculated by considering the soil-specific gravity, soil shear angle, and soil coefficient. The calculation results show that the PD reaches 12.24 kN, which gives an idea of the load that the structure has to bear. Furthermore, the internal force analysis provides a deeper understanding of the moments occurring at specific points in the structure. For example, the maximum negative moment at point A was calculated by considering the moments due to fixed load and transient load, which reached 12.73 kNm. This research contributes to improving efficiency and safety in the application of precast lining for secondary channel improvement.